2010
DOI: 10.1371/journal.ppat.1000714
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Controls Dectin-1 Expression Required for Host Antifungal Defense against Candida albicans

Abstract: We recently showed that IL-13 or peroxisome proliferator activated receptor γ (PPARγ) ligands attenuate Candida albicans colonization of the gastrointestinal tract. Here, using a macrophage-specific Dectin-1 deficient mice model, we demonstrate that Dectin-1 is essential to control fungal gastrointestinal infection by PPARγ ligands. We also show that the phagocytosis of yeast and the release of reactive oxygen intermediates in response to Candida albicans challenge are impaired in macrophages from Dectin-1 def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 35 publications
8
67
1
1
Order By: Relevance
“…Whereas the role of PPARg in modulation of IL-10 expression has been well studied (27,46), the role of TR4 was unclear. CD206 and CD36 are described as the hallmark markers for M2 macrophages (47). The ability of TR4 to modulate the expression of CD206, a M2 macrophage marker, was earlier unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the role of PPARg in modulation of IL-10 expression has been well studied (27,46), the role of TR4 was unclear. CD206 and CD36 are described as the hallmark markers for M2 macrophages (47). The ability of TR4 to modulate the expression of CD206, a M2 macrophage marker, was earlier unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Katsifa et al (21) showed that human monocytes' phagocytosis is increased through mannose receptors in response to IL-13. Later, a series of studies delineated the mechanisms of IL-13 action in a mouse model: i.e., IL-13 increases Dectin-1 and mannose receptor expression by activating PPAR-g, a critical transcription factor for M2 macrophage differentiation, which, in turn, increases M2 macrophage phagocytic activity (22)(23)(24). It is worth noting that human macrophages tend to differentiate into an M2 type in the presence of C. albicans (25), which suggests that animals possess safeguards at multiple stages of Th2 immunity against Candida infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mice that are biased toward Th2 responsiveness are more susceptible to disseminated (56) and mucosal infection (57) with Candida albicans. However, promotion of M2a polarization in gastrointestinal Candida albicans infection has been shown to limit fungal colonization (58). Finally, in lung infection with Aspergillus fumigatus, generation of Th1/regulatory T cell responses over Th2 responses favor resistance to infection (59), suggesting that M2a polarization would complicate clearance of this organism.…”
Section: Discussionmentioning
confidence: 99%